Effects of polyvinylpyrrolidone and poly (ethylene glycol) on preparation of ibuprofen pharmaceutical cocrystal - Xintong Yang; Yang Chen; Ning Qiao (Universidade de São Paulo, 2023)
Abstract In this study, we investigated the effects of polymers on the pharmaceutical cocrystal formation process. Ibuprofen (IBU) was selected as the active pharmaceutical ingredient (API), nicotinamide (NIC) and saccharin (SAC) as the cocrystal coformer (CCF), ethanol/water as the solvent, polyvinylpyrrolidone (PVP) and poly (ethylene glycol) (PEG) as the representative polymers. We prepared IBU-NIC and IBU-SAC cocrystals in ethanol-water cosolvent in the absence or presence of polymers. Cocrystal screening products were characterized by FTIR, DSC, PXRD, and HPLC. The results showed that the mixture of IBU and IBU-NIC cocrystal can be prepared in ethanol-water cosolvent without polymers. The addition of PVP facilitates the formation of pure IBU-NIC cocrystal; however, no cocrystal was formed in PEG solutions. SAC could not cocrystallize with IBU in the ethanol-water solvent in the absence of polymers. Neither PVP nor PEG could facilitate the formation of the IBU-SAC cocrystal.